Change Management to Enhance the Effectiveness on Safety School of Mahajareon Schools Networking under Sakaeo Primary Educational Service Area Office 1 - Chiwpreecha, Kesinee; Wongsangchan, Supranee; Sakulkrit , Koranut; Doungnoi, Apiprai; Chongvoranond, Phimol (Journal of Dhamma for Life, 2025)
This research aims to study the current situation and guidelines for change management to enhance the effectiveness on safety school. The sample group consisted of 97 teachers, to collect data by the questionnaires with a 5-point Likert scale and interview 5 informants by semi- structure interviews. Data analysis was conducted using frequency, percentage, mean, standard deviation, and content analysis. The research result was 1) The overall of current situation for change management to enhance the effectiveness on safety school at a high level. 2) The guidelines for change management to enhance the effectiveness on safety school (1) Strategic planning: SWOT analysis, formulate strategic plans, set goals and objectives, and develop safety systems and policies that are modern and relevant to current situations. (2) The school adheres to change management principles that emphasize participation. (3) Administrators develop leadership qualities, lead in complying with safety measures, promote a culture of safety in the school, and change management principles for effective organizational management.